Tinjauan Hukum Pengaturan Batas Usia Calon Presiden dan Calon Wakil Presiden Menurut Undang-Undang Dasar Tahun 1945: Studi Putusan Mahkamah Konstitusi Nomor 90/PUU XXI/2023 - Uoda Syahputra; Agus Adhari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia is a legal country where everything is regulated in a law and regulation, including related to the general election of presidential candidates and vice presidential candidates who regulate their requirements. This study focuses on the requirements regarding the age limit for presidential and vice presidential candidates, initially the regulation was regulated in the provisions of Article 169 letter q of Law Number 7 of 2017. Along with the times and political dynamics ahead of the 2024 elections, there is controversy related to the age limit for presidential and vice presidential candidates with the ratification of Constitutional Court Decision Number 90/PUU-XXI of 2023. So this study will further examine this controversy and discuss whether this Constitutional Court decision is appropriate or contrary to the Law. This research is a qualitative research with a normative type of research using two primary and secondary data sources. The results of this study show that basically the decision of the Constitutional Court Number 90/PUU-XXI of 2023 does not clearly violate the provisions of the law, but because it was decided ahead of the 2024 elections resulted in controversy that led to the interests of one of the presidential and vice presidential spouse candidates.